2007
DOI: 10.1007/s00192-007-0482-x
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence-related quality of life and sexual function following the tension-free vaginal tape versus the “inside–out” tension-free vaginal tape obturator

Abstract: The objective of this cohort study was to compare morbidity, quality of life, and sexual function in stress-incontinent women treated with tension-free vaginal tape (TVT) versus tension-free vaginal tape obturator (TVT-O) in a group of 329. Preoperative scores of the Urogenital Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ-7) were compared to those from a mailed, postoperative questionnaire. The Pelvic Organ Prolapse/Incontinence Sexual Questionnaire (PISQ-12) and three additional quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 35 publications
3
28
0
4
Order By: Relevance
“…Murphy et al [27] obtained similar results in a study assessing the impact of TVT versus TVT-O on sexual function in 329 women. Of the initial 329 patients, 239 (73%) with a mean follow-up of 14.7 months completed the PISQ-12.…”
Section: Impact Of Treatment For Stress Urinary Incontinence On Femalsupporting
confidence: 59%
“…Murphy et al [27] obtained similar results in a study assessing the impact of TVT versus TVT-O on sexual function in 329 women. Of the initial 329 patients, 239 (73%) with a mean follow-up of 14.7 months completed the PISQ-12.…”
Section: Impact Of Treatment For Stress Urinary Incontinence On Femalsupporting
confidence: 59%
“…While some workers may consider this outcome less important than 'objective' outcome, many studies of female stress incontinence have found subjective cure to be a more rigorous definition of success than objective cure [20] . Questionnaire-based assessment at 17 months showed a cure rate of 53% and an improvement rate of only 5%, but 42% of procedures failed to improve continence.…”
Section: Discussionmentioning
confidence: 99%
“…56,8 Several authors have therefore assessed the impact of stress urinary incontinence repair on subsequent sexual function using prospective (Table 1) and retrospective designs. [57][58][59][60][61][62] The results of most studies suggest that sexual symptoms, sexual activity and sexual function either improve or are unchanged following surgery for stress incontinence. Physical improvements of coital incontinence, urinary frequency and interference with sexual activity may be responsible for most benefit.…”
Section: Gynecological Surgery and Female Sexual Function Rn Paulsmentioning
confidence: 99%